Does an Otolaryngology-Specific Database Have Added Value? A Comparative Feasibility Analysis. (July 2016) - Bellmunt, Angela M.; Roberts, Rhonda; Lee, Walter T.; Schulz, Kris; Pynnonen, Melissa A.; Crowson, Matthew G.; Witsell, David; Parham, Kourosh; Langman, Alan; Vambutas, Andrea; Ryan, Sheila E.; Shin, Jennifer J.
Objectives: There are multiple nationally representative databases that support epidemiologic and outcomes research, and it is unknown whether an otolaryngology-specific resource would prove indispensable or superfluous. Therefore, our objective was to determine the feasibility of analyses in the National Ambulatory Medical Care Survey (NAMCS) and National Hospital Ambulatory Medical Care Survey (NHAMCS) databases as compared with the otolaryngology-specific Creating Healthcare Excellence through Education and Research (CHEER) database. Study Design: Parallel analyses in 2 data sets. Setting: Ambulatory visits in the United States. Subjects and Methods: To test a fixed hypothesis that could be directly compared between data sets, we focused on a condition with expected prevalence high enough to substantiate availability in both. This query also encompassed a broad span of diagnoses to sample the breadth of available information. Specifically, we compared an assessment of suspected risk factors for sensorineural hearing loss in subjects 0 to 21 years of age, according to a predetermined protocol. We also assessed the feasibility of 6 additional diagnostic queries among all age groups. Results: In the NAMCS/NHAMCS data set, the number of measured observations was not sufficient to support reliable numeric conclusions (percentage standard error among risk factors: 38.6-92.1). Analysis of the CHEER database demonstrated that age, sex, meningitis, and cytomegalovirus were statistically significant factors associated with pediatric sensorineural hearing loss ( P < .01). Among the 6 additional diagnostic queries assessed, NAMCS/NHAMCS usage was also infeasible; the CHEER database contained 1585 to 212, 521 more observations per annum. Conclusion: An otolaryngology-specific database has added utility when compared with already available national ambulatory databases.